TrkB promotes laryngeal cancer metastasis via activation PI3K/AKT pathway - Jiang, Liang; Wang, Zhihai; Liu, Chuan; Gong, Zhitao; Yang, Yucheng; Kang, Houyong; Li, Yanshi; Hu, Guohua (Oncotarget, 2017)
The aim of our study was to investigate the role of TrkB pathway in tumor occurrence and development for in order to provide theoretical basis to laryngeal cancer therapy. Biological characteristics of the cells were studied by migration tests and colony forming assay. Gene and protein expression analysis was performed by RT-PCR or western blot. experiments were conducted in syngeneic BALB/c mice. Significant changes in protein and gene expression, including higher expression level of TrkB, were found in cells and laryngeal cancer specimens. we demonstrated that TrkB activates AKT via c-Src, leading to increased proliferation. Also, TrkB induced EMT via increased expression of EMT related transcription factors such as Twist-1 and Twist-2. Our data indicate TrkB are overexpressed in laryngeal cancer, and TrkB signaling is involved in tumorigenicity of laryngeal cancer. These observations suggest that TrkB is a promising target for future intervention strategies to prevent tumor metastasis, EMT program in laryngeal cancer.What is already known about this subject?• Cancer of the larynx is one of the most common types of head and neck cancer.• The survival rate of advanced laryngeal cancer is only 30 to 40%.• The tropomyosin-related kinase B receptor (TrkB), together with TrkA and TrkC, are neurotrophin receptors regulating the proliferation and differentiation of neuronal cells.What are the new findings?• TrkB are overexpressed in laryngeal cancer.• TrkB signaling is involved in tumorigenicity of laryngeal cancer.• TrkB acts as a key regulator of the PI3K/AKT signal pathway-mediated tumor metastasis.How might these results change the focus of research or clinical practice?• These observations suggest that TrkB is a promising target for future intervention strategies to prevent tumor metastasis, EMT program in laryngeal cancer. Our study provides molecular insight into the tumor metastasis and has important implications in elucidating oncogenic processes.